Fatty acids and lipids : new findings - Hamazaki, Tomohito; Okuyama, Harumi (Karger, 2001)
More than 20 years ago, research on omega-3 fatty acids started from the hypothesis that fatty acids may prevent cardiovascular disease. Today, the focus has shifted and the most recent areas of research deal with the correlation between omega-3 fatty acids and behavior and mood disorders. The publication at hand gives an outline of recent advances in both of these topics, including a general discussion on fatty acid nutrition and metabolism. Moreover, issues such as vascular functions, inflammation, bone metabolism, cancer, obesity and lipoprotein metabolism are dealt with in this context. Finally, the book also contains new findings on bioactive lipids such as anandamide and related compounds, as well as on conjugated linoleic acid. Scientists interested in nutrition, cardiovascular disease, behavior and psychiatry as well as fatty acid metabolism and lipids in general will find this publication a most welcome source of information.
World review of nutrition and dietetics ; Vol. 88
Keywords: lipidy; KONGRESY /konference/; mastné kyseliny; Lipids; Fatty Acids; nutriční terapie, dietoterapie a výživa